Perceived Justice With Service Recovery, Recovery Satisfaction And Loyalty In An Airline Company: The Moderating Role Of Failure Attributions - Davoud, Nikbin (2013)
It is now well documented that an effective recovery is an essential part of firms‟ service quality programs and critical to generating satisfaction and loyalty. A number of studies have investigated the impact of recovery efforts on post-recovery satisfaction, mostly in Western countries. However, despite the importance of customer attributions of service failure; the impact of customers‟ stability and controllability attributions of failure in implementing effective recovery programs is still under study. Based on Justice Theory, this research conducted in Malaysia employed a field study to investigate how customer evaluations of recovery efforts are influenced by interplay of their failure attributions and service recovery efforts of distributive, procedural, interactional and informational justices in the context of airline company. The findings resulted from the structured questionnaire collected among 263 respondents revealed that there is a significant relationship between perceived justice and recovery satisfaction as well as loyalty in distributive and procedural justices. Recovery satisfaction was found to be affecting loyalty. The results of hierarchical regression and inclusion of failure attributions as moderator found that positive relationship between procedural and informational justices and recovery satisfaction will be higher when stability and controllability of failure is low. Finally, recovery satisfaction mediated the relationship between perceived justice in distributive and procedural justices and loyalty. The results have implication for marketing theory as well as managerial action.